Non-Born-Oppenheimer calculations of the lowest vibrational energy of HD including relativistic corrections - Stanke, Monika; Bubin, Sergiy; Molski, Marcin; Adamowicz, Ludwik (American Physical Society, 2009)
In this work we report variational calculations of the two lowest vibrational states of the HD molecule within the framework that does not assume the Born-Oppenheimer BO approximation. The nonrelativistic energies of the states were corrected for the relativistic effects of the order of 2 where = 1 c , calculated as expectation values of the operators representing these effects with the nonrelativistic non-BO wave functions. The non-BO wave functions were expanded in terms of the one-center explicitly correlated Gaussian functions multiplied by even powers of the internuclear distance. The v=0→1 transition energy obtained in the calculations is compared with the previous calculations, as well as with the transition frequency obtained from the experimental spectra. The comparison shows the need to include corrections higher than second order in to further improve the agreement between the theory and the experiment
Keywords: Physics; Non-Born-Oppenheimer calculations